Effects of a Progressive Circuit Training Program on Dribbling Performance in Adolescent Futsal Players - Muliadi; Ridho Bahtra; Hady Pery Fajri; Septri (Jurnal Master Penjas & Olahraga, 2026)
This study addressed inconsistent close ball control and slow changes of direction among adolescent players at Pariaman City Futsal Academy by examining the effects of a progressive circuit-training program on timed dribbling performance. A quasi-experimental one-group pretest-posttest design involved all 15 eligible players aged 15–18 years. Across 18 meetings, participants completed a pretest, 16 training sessions, and a posttest. The intervention used six progressive stations emphasizing zig-zag, figure-eight, shuttle, obstacle, feinting, and slalom dribbling. Mean completion time decreased from 13.53 ± 1.92 to 10.13 ± 0.74 seconds. The mean improvement was 3.40 seconds (95% CI [2.45, 4.35]), t(14) = 7.64, p < .001, with a large within-player effect (Cohen’s dz = 1.97). The program was associated with faster, more consistent dribbling, but controlled studies and match-based assessments are recommended to confirm causality and transfer to competition.